1. The problem statement, all variables and given/known data 1. Reduce the following logical expression to four literals and draw a gate level circuit, which implements the result. $$AB + BCD + BC + A \bar C$$ 2. Simplify the following: $$(A + \bar B C)(B + C)(B + \bar C)$$ 2. Relevant equations 3. The attempt at a solution I would just like to verify I understand. Here is my working for part 1: For part 2 here's what I came up with: $$(A + \bar B C)(B + C)(B + \bar C)$$ $$= (A + \bar B C)(B + C \bar C)$$ $$= (A + \bar B C)(B + 0)$$ $$= (A + \bar B C)B$$ $$= AB + \bar B B C$$ $$= AB + 0C$$ $$= AB + C$$ I think that's as simple as it can become. Thank you.